Strategi Efektif dalam Upaya Penanganan Kredit Macet BMT Maslahah Cabang Sukorejo Kabupaten Pasuruan - Mundzir, Abdillah; Islamiyah, Ulfatul; Warda, Alwiatul (Ikatan Da'i Indonesia, 2025)
Credit risk ins an inseparable aspect of financial institutions, wich can impact the operations or income of such institutions, including BMT Maslahah Sukorejo branch. This study aims to identify the strategies implemented by BMT Maslahah Sukorejo Branch in addressing the issue of non-performing loans, which poses a significant challenge for islamic financial institutions. Non-performing loans have the potential to disrupt the liquidity stability an operations of BMT Maslahah, especially in the Sukorejo Branch. The research method used is a case study with a descriptive qualitative approach, involving in-depth interviews with employees of BMT Maslahah Sukorejo Branch regarding their strategies for managing non-performing loans. The results indicate that BMT Maslahah Sukorejo Branch applies several key strategies, including rigorous evaluation in the financing approval procces, intensive monitoring of costumers, restructuring of financing for customers experiencing difficulties, and optimal use of collateral. These strategies have proven effective in reducing non-performing loans and maintaining the financial stability of BMT Maslahah Sukorejo Branch. It is recommended that BMT Maslahah Sukorejo Branch continues to develop and strengthen its financing supervision system to enhance risk management efficiency.